ANALISIS MANAJEMEN PERKREDITAN UNTUK MENINGKATKAN PROFOTABILITAS PADA PT BANK SULSELBAR DI MAKASSAR - Asnira, Asnira; Amir, Amir; Indrawahyuni, Indrawahyuni (INVOICE : JURNAL ILMU AKUNTANSI, 2019)
Research aims to determine the effectiveness and growth of indigenous revenue in the district Revenue Service Makassar City. This type of research is quantitative descriptive. The population of this research is the financial report of Makassar City District revenue office. Samples taken from the financial report of the Makassar City District revenue office in the last five years, from 2013 until 2017. Data analysis uses the ratio of effectiveness and native revenue growth, indicating that from both analyses of financial ratios are effective.